Maca (Lepidium meyenii Walpers) Andean functional food: bioactive, biochemical and biological activity - Yábar Villanueva, Emilio (2019)
Maca is nutritious, energetic and functional food. As a defense mechanism, its secondary metabolites react to biotic and abiotic stress, during pre-harvest, harvest and traditional post-harvest drying. The aim of this review is to evaluate and provide relevant scientific information about bioactives, biochemistry and biological activity of the maca (Lepidium meyenii Walpers or Lepidium peruvianum Chacón) related to health and reassess its functional food condition. A search of four electronic databases and information required from the authors was used for this review. There is a lack of in vivo and clinical research with more representative sample sizes and more consistent methodologies. Therefore, glucosinolates, phenolic compounds, phytosterols, macaenes, macamides, macahidantoins, meyeniins, alkaloids and others formed during the productive cycle of maca act synergistically to prevent chronic diseases when consumed as part of a varied diet (functional), very common in our food culture and not as isolated bioactive compounds (nutraceutical) from the biological context as pretended by the pharmaceutical industry.